THE QUALITY OF THE CHAIN (SANAD) OF HADITH CONCERNING THE LEGAL GUARDIAN (WALI) OF THE NIKAH - Saifuddin Sa’dan (PETITA: JURNAL KAJIAN ILMU HUKUM DAN SYARIAH, 2023)
Islamic Scholars have different perspectives in the interpretation of a woman's guardianship in marriage. Some scholars argue that the presence of a guardian in marriage is obligatory. On the other hand, some assert that it is not obligatory. The purpose of this study is to examine the validity of the hadith arguments used by these Islamic scholars in determining the position of the guardian in marriage. This research uses a qualitative and author examines the quality of hadith sanad (thariq takhrij sanad al-hadis) by performing jarh and ta'dil on the narrators contained in the hadith sanad in nine books of hadith (kutub al-tis'ah). The results showed that out of the five forms of traditions about marriage guardians examined from al-qutub al-tis'ah, four traditions are of saheeh (valid) quality and can be used as a source of law. While the other is of dha'if (lack) quality, then, it cannot be used as an argument in determining the law. The first hadith is masyhur, while the second, third and fourth are gharib. The fifth hadith, which explicitly forbids a woman to be a guardian in marriage for herself or another woman, is not only gharib but also dha'if in the category of shaz. Thefore, the position of the guardian in marriage for women is still a matter of debate, namely some must be present, and others need not be present of the guardian in the marriage process. Abstrak: Para ulama berbeda interpretasi dalam menetapkan adanya wali nikah pada wanita. Sebagian ulama mengatakan keberadaan wali nikah adalah wajib. Sebaliknya, sebagian lain mengatakan tidak wajib. Penelitian ini bertujuan untuk mengkaji kevalitan dalil hadis yang digunakan oleh para fuqaha tersebut dalam menentukan kedudukan wali nikah dalam pernikahan. Metode yang digunakan adalah metode penelitian kualitas sanad hadis (thariq takhrij sanad al-hadis) dengan melakukan jarh dan ta’dil terhadap para perawi yang terdapat dalam sanad hadis dalam Sembilan kitab hadis (kutub al-tis’ah). Hasil penelitian menunjukkan bahwa dari lima bentuk hadis tentang wali nikah yang diteliti dari al-qutub al-tis’a, empat hadis mempunyai kualitas shahih dan dapat dijadikan sebagai sumber hukum. Sedangkan yang satunya berkualitas dha’if, sehingga tidak boleh menjadi dalil dalam menetapkan hukum. Hadis yang pertama berstatus masyhur, sedangkan hadis kedua, ketiga dan keempat berstatus gharib. Hadis kelima yang secara tegas melarang wanita untuk menjadi wali nikah baik bagi dirinya maupun wanita lain, selain berstatus gharib juga berkualitas dha’if dengan kategori syaz. Dengan demikian, kedudukan wali dalam pernikahan bagi perempuan adalah sesuatu yang masih diperbebatkan, yaitu sebagian harus ada, sebagian lain tidak mesti ada. Kata Kunci: Hukum Islam, Hadis, Perkawinan, Fuqaha, Wali Nikah